Traumatic knee injuries and career drop-outs in adolescent competitive alpine skiers aged 15–19: a longitudinal 4-year follow-up study examining rates, biomechanical injury risk factors and potential reasons for quitting - Jonas Hanimann; Daniel P. Fitze; Thomas Koller; Flavia Schürmann; Stefan Fröhlich; Georg C. Feuerriegel; Christoph Stern; Johannes Scherr; Eling D. de Bruin; Reto Sutter; Jörg Spörri (Annals of Medicine, 2025)
Introduction The aims of this longitudinal 4-year follow-up study were (1) to assess traumatic knee injuries and career drop-out rates in competitive alpine skiers from mid- to late adolescence (i.e. 15–19 years), (2) to investigate the magnetic resonance imaging (MRI) abnormalities in the knees of skiers reaching late adolescence, and (3) to evaluate the biomechanical landing patterns of mid adolescent skiers and to compare skiers who experienced an anterior cruciate ligament (ACL) injury during the 4-years follow-up and those who did not.Materials and methods At baseline, knee flexion angle and medial knee displacement during drop jump landing were biomechanically assessed in 108 skiers aged 14.83 ± 0.58 years. During a 4-year longitudinal follow-up, 45 skiers dropped out of the study owing to lack of interest. This left a remaining cohort of 63 skiers. After 4 years, 63 skiers (aged 18.95 ± 0.64 years) were retrospectively interviewed about their knee injuries that had occurred over the past 4 years. They were also asked whether they had quit their sports careers since then and, if so, when and why. Additionally, their knee joints were imaged with MRI.Results During the 4-year follow-up, 21 skiers in the cohort of 63 skiers experienced traumatic knee injuries, 9 of whom experienced ACL injuries. Seven ACL injuries occurred in female skiers, and 2 occurred in male skiers (p = 0.044). Thirty-nine skiers (61.9%) ended their sport careers, 41.0% for health-related reasons. At baseline, female skiers who experienced ACL injury during follow-up presented smaller knee flexion angles during drop jump landing than non-injured skiers did (p = 0.013).Conclusion Between 15 and 19 years of age, one-third of competitive alpine skiers suffer from traumatic knee injury and more than half of skiers end their sports careers. In female skiers, stiff landing strategies may be considered an important but modifiable risk factor that could be targeted through systematic instructions and training.